An Interview with ChatGPT on Emergency Remote Teaching: A Comparative Analysis Based on Human–AI Collaboration - Tijen Tülübaş, Murat Demirkol, Tuncay Yavuz Ozdemir, Hakan Polat, Turgut Karakose, Ramazan Yirci (Educational Process: International Journal)
Background/purpose – ChatGPT, a recent form of AI-based language model, have garnered interest among people from diverse backgrounds with its immersive capabilities. Using ChatGPT to support or generate scientific research has also created an ongoing debate over its advantages versus risks. The present study aimed to conduct an AI-enabled research process using ChatGPT so as to evaluate its potential to generate an accurate, clear, concise, and unbiased information as these are essential elements of rigorous scientific work.